Targeting AMP‐activated kinase impacts hepatocellular cancer stem cells induced by long‐term treatment with sorafenib - Alicia Bort; Belén G. Sánchez; Pedro A. Mateos‐Gómez; Diana Vara‐Ciruelos; Nieves Rodríguez‐Henche; Inés Díaz‐Laviada (Molecular Oncology)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer death worldwide. HCC treatment is hindered by the frequent emergence of chemoresistance to the multikinase inhibitor sorafenib, which has been related to the presence of cancer stem cells (CSCs) that self‐renew and often escape therapy. The key metabolic sensor AMP‐activated kinase (AMPK) has recently been recognized as a tumour growth regulator. In this study, we aimed to elucidate the role of AMPK in the development of a stem cell phenotype in HCC cells. To this end, we enriched the CSC population in HCC cell lines that showed increased expression of drug resistance (ALDH1A1, ABCB1A) and stem cell (CD133, Nanog, Oct4, alpha fetoprotein) markers and demonstrated their stemness phenotype. These cells were refractory to sorafenib‐induced cell death. We report that sorafenib‐resistant cells had lower levels of total and phosphorylated AMPK as well as its downstream substrate, ACC, compared with the parental cells. Interestingly, AMPK knockdown with siRNA or inhibition with dorsomorphin increased the expression of stem cell markers in parental cells and blocked sorafenib‐induced cell death. Conversely, the upregulation of AMPK, either by transfection or by pharmacological activation with A‐769662, decreased the expression of ALDH1A1, ABCB1A, CD133, Nanog, Oct4, and alpha fetoprotein, and restored sensitivity to sorafenib. Analysis of the underlying mechanism points to hypoxia‐inducible factor HIF‐1α as a regulator of stemness. In vivo studies in a xenograft mouse model demonstrated that stem‐like cells have greater tumourigenic capacity. AMPK activation reduced xenograft tumour growth and decreased the expression of stem cell markers. Taken together, these results indicate that AMPK may serve as a novel target to overcome chemoresistance in HCC.